Advanced analysis of retrotransposon variation in the human genome with nanopore sequencing using RetroInspector - Javier Cuenca-Guardiola; Belén de la Morena-Barrio; Javier Corral; Jesualdo Tomás Fernández-Breis (Scientific Reports)
Abstract Transposable elements (TEs) make up 45% of the human genome, are a source of genetic variability difficult to detect, and involved in processes related to gene regulation and disease. Nanopore sequencing is recognized as one of the best technologies for detecting TEs; however, tools for analyzing of human TE insertions and deletions with nanopore-based data can be improved. RetroInspector is an easy to use, configurable Snakemake pipeline that performs detection, annotation, enrichment, and genotyping of TEs. RetroInspector requires the FASTQ files of the samples and the reference genome to start the identification and analysis of TEs. The user can also set the threshold for the number of supporting reads for the variant filtering. RetroInspector also allows users to compare the results of two samples. Different versions of the reference genome can be used and the presence of retrotransposition features can be annotated. RetroInspector has been run on three nanopore sequencing datasets and validated experimentally using proprietary and public data with over 80% precision.